2018
DOI: 10.1080/13102818.2017.1414633
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experimental hyperoxia on erythrocytes’ oxygen-transport function

Abstract: The aim of this study was to investigate the effect of hyperoxia, calcium ions and pH value on the composition of major phospholipids in human erythrocyte membranes and erythrocytes' oxygentransport function. To create a model of hyperoxia, we saturated the incubated mixture with oxygen by constant passing of oxygen-air mixture through the incubation medium. To assess the effect of elevated calcium ion concentrations, CaCl 2 was added to the incubation medium. An incubation medium with different pH was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…The search terms comprised of two pairs (a) membrane composition OR phospholipid composition AND (b) human erythrocyte OR human red blood cell; each pair being combined using a Boolean OR operator, and then a total AND combinator to yield 23 results, of which only 9 were appropriate for inclusion. [128][129][130][131][132][133][134][135][136] One important note on the erythrocyte data; only 2 of the 9 compositions contained data that related to cholesterol content, and as such it may not be completely representative. However, where cholesterol contents were reported, the amounts of other lipids were reduced in all cases compared to where they were not reported.…”
Section: Human Erythrocyte Membrane Compositionmentioning
confidence: 99%
“…The search terms comprised of two pairs (a) membrane composition OR phospholipid composition AND (b) human erythrocyte OR human red blood cell; each pair being combined using a Boolean OR operator, and then a total AND combinator to yield 23 results, of which only 9 were appropriate for inclusion. [128][129][130][131][132][133][134][135][136] One important note on the erythrocyte data; only 2 of the 9 compositions contained data that related to cholesterol content, and as such it may not be completely representative. However, where cholesterol contents were reported, the amounts of other lipids were reduced in all cases compared to where they were not reported.…”
Section: Human Erythrocyte Membrane Compositionmentioning
confidence: 99%
“…Other studies determine: • The obtained results indicated that hyperoxia causes deep changes both in the composition and character of bilayer lipids of erythrocyte membranes, which affects the functional characteristics of erythrocytes, primarily the oxygen-transport properties of erythrocyte haemoglobin [9];…”
mentioning
confidence: 94%
“…It should be stressed that the erythrocytic part of the blood system is the first to respond to activation of free radical oxidation and the first to exhaust their compensatory function [9]. Hyperoxia in vitro upregulates LPO in erythrocyte membranes and modifies lipid composition and functional parameters of erythrocytes -first of all, the oxygen transporting properties of hemoglobin [15].…”
mentioning
confidence: 99%